Resource and digital technology use in itinerant teachers in Costa Rica - Paniagua-Esquivel, Cristina (Innovaciones Educativas, 2022)
Itinerant teachers are known for supporting students with learning problems, disabilities, and emotional issues, and they even help other teachers that teach foreign languages and complementary courses. For these teachers, who sometimes work in five different schools at a time, it is vital to have a high-level design of digital resources. However, information about these resources has not been found. The present article is part of the 1st National Census of Digital Technologies in Education organized and developed by the Costa Rican Ministry of Public Education in collaboration with Universidad de Costa Rica in 2016 and 2017. This census-like quantitative research obtained its data from 1019 itinerant teachers. The instrument was a self-administered questionnaire sent by the online survey platform LimeSurvey. Descriptive statistics and the Spearman correlation coefficient were used to show the level of use of digital teaching resources, which is one of the digital skills, and its relationship with attitude and training. The main result reveals that most itinerant teachers use digital resources in their teaching practice and have an intermediate to advanced level in using them, along with a high attitude and a low level of training. Although the relationship with these technologies is weak, it is worth reflecting on so it can be increased in potential courses and for future access to resources.